2020
DOI: 10.1051/epjconf/202023702017
|View full text |Cite
|
Sign up to set email alerts
|

Is Near-Spherical Shape “the New Black” for Smoke ?

Abstract: We present smoke lidar measurements from the Canadian fires of 2017. The advected smoke layers over Europe are detected at both tropospheric and stratospheric heights, with the latter presenting non-typical values of the Particle Linear Depolarization Ratio (PLDR) with strong wavelength dependence from the UV to the Near-IR. Specifically, the PLDR values are of the order of 22, 18 and 4% at 355, 532 and 1064 nm respectively. In an attempt to interpret these results, we apply the hypothesis that smoke p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…lidar measurements in Central (Ansmann et al, 2018;Q. Hu et al, 2019) and South Europe (Gialitaki et al, 2019;Sicard et al, 2019) revealed high PLDR values at 355 and 532 nm and a strong spectral dependence from the UV to the Near-IR.…”
Section: Introductionmentioning
confidence: 99%
“…lidar measurements in Central (Ansmann et al, 2018;Q. Hu et al, 2019) and South Europe (Gialitaki et al, 2019;Sicard et al, 2019) revealed high PLDR values at 355 and 532 nm and a strong spectral dependence from the UV to the Near-IR.…”
Section: Introductionmentioning
confidence: 99%
“…Once there, the new particle is let loose from infinity and joined to the expanding cluster. The model was investigated both on and off the lattice in multiple dimensions d 2; DLA has garnered a lot of attention throughout the years as a stunning illustration of fractal objects [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].This is a research report on diffusion-limited Aggregation. Diffusion-limited aggregation is a process in which particles of matter stick together (aggregate) as they chaotically move (diffuse) through a medium that provides some sort of resistive (limiting) force.…”
Section: Introductionmentioning
confidence: 99%
“…"Diffusion" refers to the random movement of the particles that make up the structure before they adhere ("Aggregate") to it. "Diffusion-limited" refers to the fact that the structure grows one particle at a time rather than in chunks of particles because the particles are thought to be in low concentrations, preventing them from coming into touch with one another [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Other instances include the development of coral, the route of lightning, the coalescence of dust or smoke particles, and the development of certain crystals.…”
Section: Introductionmentioning
confidence: 99%